PENGARUH PEMBERIAN AIR REBUSAN DAUN SIRIH HIJAU TERHADAP KEJADIAN KEPUTIHAN - Cecilya Kustanti (Jurnal Keperawatan Notokusumo, 2017)
Background: Whiteness in adolescents is often found in adolescents who are less concerned with the cleanliness and maintenance of regional genetalia. High levels of whiteness in women and girls in the world and in Indonesia, as well as fatal impacts if left untreated. Correctly so we need a way / strategy to overcome leucorrhoea, one of them with boiled water of green betel leaves that have efficacy without side effects. Objective: To know the effect of Water Decoction of Green Betel Leaf against the occurrence of leucorrhoea. Method: This study used experimental quasi experimental method (experimental quasi) or experimental research design with Time Series Design Design Design.Treatment of 30 respondents, 20 control respondents conducted in Turen Village, Canden, Jetis, Bantul, Yogyakarta April 2016 and implementation of activities in June 2016 and completion of the report in July 2016 Result: Based on the analysis of the average decrease in the rate of real water decomposition of Boiling Water Green Leaves was statistically significant with p = 0.001 p (= 0.05) between the treatment group and the control group. The decrease in whiteness occurred in the treatment group -12,8290 from pre-test to post-test. Conclusion: The provision of Green Betel Leaf Rinse has an influence on decreasing the level of discharge experienced by young women.